Pregnancy in women with history of ischemic stroke and thrombophilia - A. D. Makatsariya; S. V. Akinshina; V. O. Bitsadze; E. V. Zhuravleva; L. E. Idrisova; G. R. Abramyan (Акушерство, гинекология и репродукция)
Currently due to reduction of direct causes of maternal mortality increasing interest of scientists cause arterial thrombotic complications. Pregnancy-related stroke is a rare event, however, when it occurs, may be life threatening and there may be implications for management of the patient and delivery. The mechanisms and risk factors for ischemic stroke related to pregnancy and in women of childbearing age remain unclear. Pathogenesis of so severe complication in young women is not fully understood, however, there is a concept thrombosis or cerebral embolism, which can develop on the background of well-known population-based risk factors such as hypertension, metabolic syndrome, smoking, heart rhythm disorders, valvular heart disease or in relation to typical obstetric pathologies, such as preeclampsia, massive obstetrical bleeding, septic complications, amniotic fluid embolism. In recent years, there is increasing interest in the role of thrombophilia in the pathogenesis of ischemic stroke, however, data on this issue is even more limited and contradictory than for venous thrombosis. Methods of prevention of recurrent stroke and strategies of pregnancy and delivery management in women with history of ischemic stroke are also contradictory.